Sơ bộ đánh giá dư lượng một số thuốc giảm đau không thuộc nhóm steroid trong nước thải Hà Nội - Đức, Lê Minh; Quân, Nguyễn Văn; Anh, Dương Hồng; Trang, Phạm Kim; Việt, Phạm Hùng (Vietnam Journal of Chemistry, 2016)
In this report, the simultaneous determination procedure of four nonsteroidal anti-inflammatory drugs (NSAIDs): ibuprofen, bezafibrate, naproxen, diclofenac in wastewater was applied to 20 wastewater samples collected in Hanoi. The procedure for analysis of these NSAIDs is including two steps: first extraction/trace enrichment by solid phase extraction method and then followed by quantitative determination by portable automated capillary electrophoresis (CE) equipment with capacitively coupled contactless conductivity detector (C4D). The obtained analysis result showed the presence of ibuprofen in 12 samples with concentrations ranging from 6.98-38.7 μg/L and bezafibrate in only 1 sample with concentration of 45.3 μg/L. The CE-C4D method was cross-checked by the high-performance liquid chromatography method (HPLC) with DAD detector, the deviation of the result obtained by CE-C4D compared to those with the standard reference method (HPLC-DAD) was less than 20 %. Keywords. Capillary electrophoresis, anti-inflammatory drugs, Hanoi wastewater